Family Risk Factors Associated With Oppositional Defiant Disorder Symptoms, Depressive Symptoms, and Aggressive Behaviors Among Chinese Children With Oppositional Defiant Disorder - Lin, Xiuyun; Li, Yanbin; Xu, Shousen; Ding, Wan; Zhou, Qing; Du, Hongfei; Chi, Peilian (Frontiers in Psychology, 2019)
Family factors including parent emotion dysregulation and harsh parenting practices place children at high risk for malfunctioning in emotion regulation, depressive symptoms and aggressive behaviors. This study investigated the associations among parent emotion dysregulation, harsh parenting practices (i.e., emotional abuse and corporal punishment), and child emotion regulation and child oppositional defiant disorder (ODD) symptoms, and co-occurring depressive symptoms and aggressive behaviors. Participants were 239 parent-child dyads from 14 primary schools in Mainland China. All children were diagnosed with ODD. Parent emotion dysregulation, harsh parenting practices, child emotion regulation were reported by parents; child ODD symptoms were reported by parents and teachers; child depressive symptoms were reported by children; child aggressive behaviors were reported by teachers. Data indicated that parent emotion dysregulation was related to child ODD symptoms in the home and depressive symptoms indirectly through harsh parenting practices and child emotion regulation. Harsh parenting practices were related to child ODD symptoms in the home directly and indirectly through child emotion regulation. Moreover, emotional abuse was associated with child depressive symptoms directly and indirectly through child emotion regulation. Our findings highlighted the need for prevention and intervention targeting parent emotion dysregulation and harsh parenting practices among children with ODD.